National kayak-canoe team high altitude training methods - Xu, J.; Jin, L. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This study tested the use of scientific theories, exercise physiology, and sports biochemistry methods in high altitude training of national kayak and canoe team athletes for the purpose of helping coaches and athletes to improve the effectiveness of high altitude training and recovery, as well as to provide the theoretical base and empirical evidence for scientifically developing training programs and for improving training and performance. Methods The research was conducted with 24 national athletes over an 18-week training period, divided into four phases of varying training intensities designed to improved endurance and performance. Physiological and biochemical testing, such as, lactate and heart rate tests, were performed regularly and all data were analyzed by COMPAQ Persario 7222 computer. Results The results showed that: (1) Long-term monitoring of Hb, BUN, weight, and lactate indicated how athletes adapt to and recover from training loads. A too heavy a training impact on the body was indicated when Hb decreased, BUN increased and body weight decreased. Appropriate training loads were indicated when Hb returned to normal, BUN decreased and weight was stabilized. (2) Athletes who had higher Hb levels before competition performed better in the 500 and 1000 meter events-indicating that Hb alterations are indicators of adaptability and aerobic ability levels. (3) Improving training programs and adjusting protein intake were ways to stem weight reductions during altitude training. (4) Improvement of oxygen transportation ability was indicated when the morning pulse rate, systolic pressure and diastolic pressure all decreased at the same time. (5) Athletes' lactate levels increased during altitude training. Lactate levels were higher upon returning to regular plateau training as compared to pre-altitude training levels. The ratio of anaerobic energy to aerobic energy increased as a result of altitude training. (6) Recovery cycles were shorter after altitude training. After four weeks of altitude training, athletes like Beibei Gao and Guangliang Meng were able to achieve their best performance in the 500 m. and 1000 m. events. Conclusion (1) Hb, BUN, weight and lactate data can be used to determine the effectiveness of athletic training programs and to improve understanding of the principles of kayak-canoe training and improvement of the sport. (2) Altitude training is an effective training method for developing athletic endurance and improving aerobic and anaerobic abilities. (3) Altitude training shortens the recovery cycle of athletes.